The mechanisms underlying the actions of Xuefu Zhuyu decoction pretreatment against neurological deficits after ischemic stroke in mice: The mediation of glymphatic function by aquaporin-4 and its anchoring proteins - Yi, Ting; Gao, Ping; Hou, Meng; Lv, Huan; Huang, Mengyuan; Gao, Shanshan; He, Jinrong; Yang, Dongdong; Chen, Weiyin; Zhu, Tianmin; Yu, Chang; Liu, Fuyou; et al. (Frontiers in Pharmacology, 2022)
Ischemic stroke (IS) has been associated with an impairment in glymphatic function. Xuefu Zhuyu Decoction (XFZYD) is widely used in the prevention and treatment of IS. We hypothesized that XFZYD pretreatment could attenuate early neurological deficits after IS by enhancing the function of the glymphatic system. To prove our hypothesis, we carried out temporary middle cerebral artery occlusion and reperfusion surgery on C57BL/6 mice and then measured neurological score, infarct size and performed hematoxylin-eosin staining to assess stroke outcomes after 24 h of reperfusion. Subsequently, we injected fluorescent tracers in to the cisterna magna and evaluated tracer distribution in coronal brain sections. The polarization of aquaporin-4 (AQP4), colocalization of AQP4, α-dystroglycan, β-dystroglycan and agrin were determined by immunofluorescence. Our research showed that pretreatment with XFZYD significantly alleviated neurological scores, neurological deficits and pathological abnormalities in a mouse model of IS. Importantly, XFZYD pretreatment enhanced CSF influx, protected AQP4 depolarization and promoted the colocalization of AQP4 with its anchoring proteins in the brain. Our findings highlight novel mechanisms underlying the neuroprotective effect of XFZYD pretreatment on IS-induced brain damage through the glymphatic system. XFZYD pretreatment may offer a promising approach to slow the onset and progression of IS.